The Influence Of Organizational Culture And Utilization Of Accounting Information Systems On Managerial Performance - Aulia Gusmiarni; Sudrajat Sudrajat (Yayasan Riset dan Pengembangan Intelektual, 2023)
The occurrence of a fairly high inflation rate in Lampung Province in the second quarter of 2022 has had an impact on aspects of people's lives. This affects the priority scale of needs that must be met by the community. BPJS Kesehatan Bandar Lampung Branch Office is one of the organizations affected. Based on the target achievement report as of December 2022, information was obtained that the achievement of participant contributions was less than the predetermined target. In achieving goals, employees as operational actors play an important role. The existence of an organizational culture is balanced by the existence of an optimal accounting information system that can produce good productivity. This research was conducted at the BPJS Kesehatan Bandar Lampung Branch Office. The method of determining the research sample is based on a saturated sampling technique with a sample of 83 employees. The research instrument used was a questionnaire with data analysis techniques used including data quality tests, data statistical tests, and hypothesis testing. The results showed that organizational culture and utilization of accounting information systems had a positive effect on improving the managerial performance of employees working at the BPJS Kesehatan Bandar Lampung Branch Office.